6x*6=-6

Simple and best practice solution for 6x*6=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x*6=-6 equation:


Simplifying
6x * 6 = -6

Reorder the terms for easier multiplication:
6 * 6x = -6

Multiply 6 * 6
36x = -6

Solving
36x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '36'.
x = -0.1666666667

Simplifying
x = -0.1666666667

See similar equations:

| y-(-4)=5(x-3) | | -19+x=14 | | 17.8x+5[6-(2x+3)]= | | P^2+2p-24= | | -(1-(-2)2)2-5x(-2)= | | 324=2X+(X-84) | | 24+7x=9x+14 | | x-(-11)=17 | | y+4x-2=0 | | -6x-10=19-5x | | 13+x=-20 | | 3*4.5-y=9 | | 2x^2+3y^2+12x-12y-210=0 | | 7(2x+9)=3x+100 | | 6+3*5-2=18 | | 5(3x-6)=12 | | 19=23-2v | | -2(4x-2)+6x=4(x+3) | | 4m-9= | | 6+3*5-2=5 | | 2(3x+2)+6(2x-1)=40 | | 13x-4=2x+4 | | -72=-8(4-2x)-8(1-2x) | | 13x-4=2x+2 | | 2p=96-10 | | 5p-7p=3p+1 | | 13x+4=-5x+1 | | -86=-2(1-6a) | | 6sqrtx=x | | -5(-3v+5)-8v=3(v-5)-4 | | 13x+4=-5x-3 | | 2m+3m=4m-9 |

Equations solver categories